Surface coated cutting tools

The surface-coated cutting tool with a layered Al-Ti composite nitride/carbonitride structure addresses abnormal wear and chipping issues, ensuring durable cutting performance in high-speed intermittent alloy steel cutting.

JP7610181B2Active Publication Date: 2025-01-08MITSUBISHI MATERIALS CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021052999
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-26
Publication Date
2025-01-08
Estimated Expiration
2041-03-26

AI Technical Summary

Technical Problem

Coated tools with Ti-Al-based composite carbonitride layers exhibit abnormal wear and chipping during high-speed intermittent cutting of alloy steel, leading to unsatisfactory cutting performance.

Method used

A surface-coated cutting tool with a composite nitride or carbonitride layer containing Al and Ti, featuring a layered structure with α and β layers, where the α layer has a NaCl-type face-centered cubic structure and the β layer has a wurtzite hexagonal structure, enhancing chipping resistance.

Benefits of technology

The tool achieves long-lasting cutting performance with improved chipping resistance and wear resistance during high-speed interrupted cutting of alloy steel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007610181000015
    Figure 0007610181000015
  • Figure 0007610181000001
    Figure 0007610181000001
  • Figure 0007610181000002
    Figure 0007610181000002
Patent Text Reader

Abstract

To provide a surface-coated cutting tool exerting excellent cutting performance even when using the tool for high-speed intermittent cutting work of an alloy steel or the like.SOLUTION: In a surface-coated cutting tool in this invention, a coating layer has one or more of the laminate layer consisting of a laminate unit layer including α layer of a tool substrate side and β layer of a tool surface side. The α layer has an average layer thickness of 1.0 to 20.0 μm and includes the layer whose average composition is (AlxαTi1-xα)(CyαN1-yα) (here, xα:0.60-0.95 and yα:0.000-0.015), and a crystal grain area percentage of cubic crystal is 70% or more. The β layer has the average layer thickness of 0.5 to 5.0 μm and includes the layer in which its average composition is AlxβMeyβCzβN1-xβ-yβ-zβ(here, Me is one or more of Ti, Si, Zr, V, Cr, Nb, Hf and Mn); xβ / (xβ+yβ) is 0.70-0.95; zβ / (xβ+yβ) is 0.15∼3.00; and xβ+yβ is 0.15-0.60. The area ratio of the sum of grains of hexagonal and cubic crystals is less than 30%.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a surface-coated cutting tool (hereinafter sometimes referred to as a coated tool).

Background Art

[0002] Conventionally, there has been a coated tool in which a Ti-Al-based composite carbonitride layer is coated and formed as a coating layer on the surface of a tool substrate such as tungsten carbide (hereinafter referred to as WC) - based cemented carbide, and these are known to exhibit excellent wear resistance. And although these are relatively excellent in wear resistance, various proposals have been made for improving the coating layer because abnormal wear such as chipping is likely to occur when used under high-speed interrupted cutting conditions or the like.

[0003] For example, Patent Document 1 discloses a coating tool having a multilayer structure in which a first unit layer composed of Ti 1-x Al x N and a second unit layer composed of Ti 1-y Al y N are alternately laminated, the first unit layer has an fcc-type crystal structure and 0 < x < 0.65, the second unit layer has an hcp-type crystal structure and 0.65 ≦ y < 1, and the thicknesses of each of the first unit layer and the second unit layer are 3 to 30 nm. The coated tool is described as having high hardness and high oxidation resistance.

[0004] Further, for example, Patent Document 2 discloses a structure including a plurality of crystal grains and an amorphous phase between the crystal grains. Each of the crystal grains has a Ti 1-x Al x N layer having an fcc structure and a Ti 1-y Al y N layer having an hcp structure alternately laminated, satisfying the relationship of 0 ≦ x < 1, 0 < y ≦ 1, (y - x) ≧ 0.1. The amorphous phase contains at least one of carbides, nitrides or carbonitrides of Ti and Al, and the thickness per layer of each of the adjacent Ti 1-x Al x N layer and the Ti 1-y Aly A coated tool having a coating with a total thickness of 1 to 50 nm including the thickness of each of the N layers is described, and the coated tool is said to have a long life.

[0005] In addition, for example, Patent Document 3 describes a coated tool having a lower layer made of a titanium aluminum nitride coating mainly having an fcc structure and a thickness of 2 to 15 μm, and an upper layer made of an aluminum nitride coating having an hcp structure and a thickness of 0.2 to 10 μm, wherein the upper layer has a columnar crystal structure, the columnar crystals have an average cross-sectional diameter of 0.05 to 0.6 μm, and the ratio of the X-ray diffraction peak value Ia(100) of the (100) plane to the X-ray diffraction peak value Ia(002) of the (002) plane in the upper layer satisfies the relationship Ia(002) / Ia(100)≧6, and the upper layer is epitaxially grown on the lower layer, and the coated tool is said to have excellent chipping resistance and coating adhesion. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2015-124407 A [Patent Document 2] JP 2016-3369 A [Patent Document 3] International Publication No. 2018 / 008554 Summary of the Invention [Problem to be solved by the invention]

[0007] As a result of investigations, the present inventors have recognized that when the coated tools described in Patent Documents 1 to 3 are used in high-speed intermittent cutting of alloy steel, abnormal damage such as thermal cracks occurs in the coating (coating layer) on the rake face of the coated tool, which is prone to chipping starting from such abnormal damage, and therefore the coated tools cannot be said to exhibit satisfactory cutting performance.

[0008] Therefore, an object of the present invention is to provide a coated tool which exhibits excellent cutting performance over a long period of use, particularly when used for high-speed intermittent cutting of alloy steel or the like, by providing a coating layer with excellent chipping resistance. [Means for solving the problem]

[0009] The present inventors have intensively investigated the composition and crystal structure of the coating layer and have found that A layer of a predetermined thickness of a composite nitride layer or composite carbonitride layer containing Al and Ti having a predetermined ratio of crystal grains having a NaCl type face-centered cubic structure (hereinafter, this composite nitride layer or composite carbonitride layer is also referred to as an AlTiCN layer) on the side of the tool substrate, A layer of a predetermined thickness of a composite carbide layer or composite carbonitride layer (hereinafter, this composite carbide layer or composite carbonitride layer is also referred to as an AlMeCN layer) containing Al and Me (wherein Me is one or more elements selected from Ti, Si, Zr, V, Cr, Nb, Hf, and Mn) in which the total ratio of crystal grains having a wurtzite-type hexagonal crystal structure (hereinafter, sometimes referred to as a hexagonal crystal structure) and crystal grains having a NaCl-type face-centered cubic structure (hereinafter, sometimes referred to as a cubic crystal structure) is set to a predetermined value or less is formed on the tool surface side. When a coating layer including a laminate in which one or more of the lamination unit layers are laminated is provided, We have gained the new knowledge that chipping resistance is improved even in high-speed intermittent cutting of alloy steel.

[0010] The present invention is based on this finding, "(1) A surface-coated cutting tool having a tool base and a coating layer provided on the surface of the tool base, 1) The coating layer has one or more laminate layers, each of which has an α layer on the tool substrate side and a β layer on the tool surface side as a laminate unit layer, 2) The α layer includes a composite nitride layer or composite carbonitride layer of Al and Ti having an average layer thickness of 1.0 to 20.0 μm, and the average composition of the layer is represented by the formula: (Al xα Ti 1 -xα )(C yα N 1-yα), xα is 0.60 to 0.95, yα is 0.000 to 0.015, 3) The area ratio of crystal grains having a NaCl type face-centered cubic structure in the α-phase is 70% or more, 4) The β layer includes a composite carbide layer or composite carbonitride layer of Al and Me (Me is one or more elements selected from Ti, Si, Zr, V, Cr, Nb, Hf, and Mn) having an average layer thickness of 0.5 to 5.0 μm, and the average composition is represented by the formula: Al xβ Me yβ C zβ N 1-xβ-yβ-zβ When expressed as above, xβ / (xβ+yβ) is 0.70~0.95, zβ / (xβ+yβ) is 0.15~3.00, and xβ+yβ is 0.15~0.60. 4) The total area ratio of crystal grains of a wurtzite type hexagonal crystal structure and crystal grains of a NaCl type face-centered cubic structure in the β phase is less than 30%; A surface-coated cutting tool comprising: (2) The surface-coated cutting tool according to (1) above, characterized in that the rake face of the surface-coated cutting tool has a coating layer including an α layer and a β layer, and the flank face has a coating layer including only an α layer. (3) the α layer has a columnar crystal structure, and the average grain width W of the columnar crystal grains is 0.1 to 1.2 μm; Area-weighted average The surface-coated cutting tool according to (1) or (2) above, characterized in that the average aspect ratio A is 2.0 to 10.0." It is. Effect of the Invention

[0011] The surface-coated cutting tool according to the present invention has a long life even when used in high-speed interrupted cutting of alloy steel. [Brief description of the drawings]

[0012] [Figure 1] FIG. 2 is a schematic diagram showing a coating layer when there is one laminate layer, the laminate layer having an α layer on the tool substrate side and a β layer on the tool surface side as a laminate unit layer, in an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, the coated tool according to the embodiment of the present invention will be described in more detail. In the claims and this specification, when a numerical range is expressed using "L to M" (where L and M are both numerical values), the range includes the upper limit (M) and the lower limit (L), and the units of the lower limit and the upper limit are the same.

[0014] Coating layer structure (overall structure) As shown in Fig. 1, the coated tool according to this embodiment has a tool base (1) and, as a coating layer, one or more laminate layers having an α layer (AlTiCN layer) (2) on the tool base side and a β layer (AlMeCN layer) (3) on the tool surface side as laminate unit layers. The embodiment shown in Fig. 1 has one laminate multilayer.

[0015] With such a coating layer structure, it is possible to achieve excellent cutting performance over a long period of time even in high-speed intermittent cutting of alloy steel. Although the reason for this is unclear, it is assumed to be due to the wear resistance of the β layer of the α layer (AlTiCN layer) and the toughness of the β layer (AlMeCN layer).

[0016] In addition, the coating layer may include at least one laminate layer formed by laminating the lamination unit layers of the α layer and the β layer, and may further include other layers, such as a base layer that improves adhesion between the laminate layer and the tool base, or an upper layer that does not promote wear, such as chipping, on the laminate layer.

[0017] The underlayer may be at least one of a Ti carbide layer, a nitride layer, a carbonitride layer, a carbonate layer, and a carbonitride-oxycarbonitride layer, and the upper layer may be at least one of a Ti carbonitride-oxycarbonitride layer and an aluminum oxide layer. The compositions of these layers are not necessarily limited to those within the stoichiometric range, but may include any conventionally known atomic ratio.

[0018] The average thickness of the entire coating layer, including the undercoat layer and the upper layer, is preferably in the range of 1.5 to 25.0 μm. The reason for this range is that if it is less than 1.5 μm, the properties of the coating layer provided by the properties of the α layer and the β layer may not be fully exhibited, while if it exceeds 25.0 μm, the chipping resistance may decrease. In the claims and this specification, the average layer thickness refers to the average thickness measured at the rake face.

[0019] The α layer and the β layer will be described in detail below.

[0020] 1.α layer The α layer is as follows:

[0021] (1) Average layer thickness The average layer thickness Lα of the α layer is preferably 1.0 to 20.0 μm. This is because, within this range, sufficient wear resistance can be ensured and excellent chipping resistance can be obtained. When the average layer thickness is 3.0 to 20.0 μm, the above-mentioned properties can be exhibited even more. When there are a plurality of laminate layers of α layers and β layers, the thicknesses of the α layers may be the same or different as long as they are within the above range.

[0022] (2) Composition The average composition of the α layer is expressed by the formula: (Al xα Ti 1 -xα )(C yα N 1-yα ), the average content ratio xα of Al in the total amount of Ti and Al and the average content yα of C in the total amount of C and N (where xα and yα are both atomic ratios) are preferably 0.60 to 0.95 and 0.000 to 0.015, respectively.

[0023] The reason for setting the average Al content within this range is that if it is less than 0.60, the AlTiCN layer is inferior in hardness and has insufficient wear resistance, while if it exceeds 0.95, the Ti content decreases, making it easier for crystal grains with a hexagonal crystal structure to be contained, resulting in reduced wear resistance. The reason why the average C content is set to this range is that sufficient wear resistance can be ensured within this range.

[0024] (3) Crystal structure The α layer contains crystal grains of a complex nitride or complex carbonitride of Al and Ti having a NaCl-type face-centered cubic structure (cubic crystal structure). Here, the α layer having a cubic crystal structure means that it has 70% or more by area of ​​crystal grains with a cubic crystal structure on a longitudinal section (in the case of an insert, a section perpendicular to the flat surface when the surface of the tool base is treated as a flat surface, ignoring minute irregularities on the surface; in the case of a shank tool, a section perpendicular to the cutting edge). When this area ratio is satisfied, the α layer can more reliably exhibit its properties of good hardness and excellent wear resistance. It is more preferable that the crystal grains with a cubic crystal structure account for 90% or more by area, and it may even be 100% by area.

[0025] (4) Average particle width and aspect ratio It is more preferable that the material has a columnar crystal structure, the columnar crystal grains having an average grain width W of 0.1 to 1.2 μm and an average aspect ratio A of 2.0 to 10.0. The reason is that the presence of a columnar crystal structure having an average grain width of 0.1 to 1.2 μm and an average aspect ratio of 2.0 to 10.0 can suppress abnormal damage to a cutting tool during cutting.

[0026] 2.β layer The β layer is as follows:

[0027] (1) Average layer thickness The average thickness Lβ of the β layer is preferably 0.5 to 5.0 μm. This is because the wear resistance of the rake face can be sufficiently ensured within this range, and the β layer has excellent thermal crack resistance and chipping resistance. When there are multiple laminate layers of α layers and β layers, the thicknesses of the β layers may be the same or different as long as they are within the above range.

[0028] (2) Composition The average composition of the β layer is expressed by the formula: (Al xβMe yβ C zβ N 1-xβ―yβ―zβ ), it is preferable that the average content ratio of Al in the total amount of Me and Al, xβ / (xβ+yβ), is 0.70 to 0.95, the average content ratio of C in the total amount of Al and Me, zβ / (xβ+yβ), is 0.15 to 3.0, and the sum of the average content ratio of Al and the average content ratio of Me, xβ+yβ, is 0.15 to 0.60 (where xβ, yβ, and zβ are all atomic ratios).

[0029] The reason for setting the average Al content ratio xβ / (xβ+yβ) in the above range is that if it is less than 0.70, the heat crack resistance brought about by the inclusion of Al decreases, while if it exceeds 0.95, the wear resistance decreases.

[0030] Furthermore, if the average content of C, zβ / (xβ+yβ), falls within the above range, the lubricity and wear resistance are improved. Furthermore, if xβ+yβ, which is the sum of the average Al content and the average Me content, is less than 0.15, the heat crack resistance is insufficient, whereas if it exceeds 0.60, the wear resistance is reduced.

[0031] (3) Crystal structure The β layer contains a composite carbide or composite carbonitride of Al and Me in which the total area ratio of crystal grains having a wurtzite-type hexagonal crystal structure and crystal grains having a NaCl-type face-centered cubic structure is less than 30%. Here, the total area of ​​the hexagonal and cubic structures in the β-layer is less than 30% by area, which means that the total area of ​​the crystal grains having these structures is less than 30% by area in the longitudinal section. If this area ratio is satisfied, the amorphous phase or fine crystal grains increase, and the β-layer can reliably exhibit its excellent thermal crack resistance.

[0032] 3. The coating layer on the rake face contains α and β layers, while the coating layer on the flank face contains only α layers. It is preferable to provide a coating layer having a laminated structure including an α layer and a β layer on the flank face, and to provide a coating layer including an α layer but not including a β layer on the surface of the flank face. Although a β layer may be provided on the flank face, the absence of a β layer, which has low wear resistance, can prevent the underlying α layer from falling off together with the β layer, and the tool life is further improved. A means for making the surface of the flank face only an α phase is to perform a known surface treatment such as a brush treatment or a blast treatment on the tool surface after the coating from the flank face direction to remove the β layer.

[0033] 4. Measurement of average layer thickness, composition, and crystal structure (area ratio) of α and β layers First, a longitudinal section is prepared by polishing the coating layer using a focused ion beam system (FIB), a cross section polisher (CP), etc. Then, in this longitudinal section, a square with a thickness of the coating layer in the direction perpendicular to the surface of the tool base (layer thickness direction) and a width of 100 μm parallel to the tool base is set as a measurement region, and an electron backscatter diffraction image is obtained by irradiating the measurement region with an electron beam of 15 kV acceleration voltage at an incident angle of 70 degrees and an irradiation current of 1 nA at intervals of 0.01 μm using an electron backscatter diffraction analyzer (EBSD), and the boundaries of regions with different crystal structures are defined from the structural analysis results of each measurement point (hereinafter sometimes referred to as pixels).

[0034] Here, the direction perpendicular to the surface of the tool base (layer thickness direction) is the direction perpendicular to the average line of the roughness curve at the interface between the tool base and the coating layer in an observation image of a longitudinal section, when the average line of the roughness curve is taken as the surface of the tool base.

[0035] That is, when the tool base has a flat surface like an insert, element mapping is performed on the longitudinal section using energy dispersive X-ray spectroscopy (EDS), and the obtained element map is subjected to known image processing to determine the interface between the coating layer (if a lower layer, described later, exists, the lower layer is used instead of the coating layer) and the tool base, and the average line of the roughness curve of the interface between the coating layer and the tool base thus obtained is arithmetically determined, and this is regarded as the surface of the tool base. Then, within the plane of the longitudinal section, the direction perpendicular to this average line is regarded as the direction perpendicular to the tool base (layer thickness direction).

[0036] Furthermore, even if the tool base has a curved surface like a drill, if the tool diameter is sufficiently large compared to the thickness of the coating layer, the interface between the coating layer and the tool base in the measurement area will be approximately flat, and the surface of the tool base can be determined using a similar technique.

[0037] That is, for example, in the case of a drill, element mapping is performed using EDS on the longitudinal section of the coating layer in a section perpendicular to the axial direction, the obtained element map is subjected to known image processing to determine the interface between the coating layer and the tool base, and the mean line is arithmetically obtained for the roughness curve of the interface between the coating layer and the tool base thus obtained, which is regarded as the surface of the tool base. Then, within the plane of the longitudinal section, the direction perpendicular to this mean line is regarded as the direction perpendicular to the tool base (layer thickness direction).

[0038] In the present invention, the region that does not have a hexagonal crystal structure or a cubic crystal structure refers to a region that does not have a long-period structure like a crystal, for example, and refers to a region in which a halo pattern specific to an amorphous material or discrete diffraction spots equivalent thereto are obtained.

[0039] Furthermore, the α layer and the β layer are identified based on the composition analysis results obtained by performing line analysis in the layer thickness direction using Auger Electron Spectroscopy (AES) and Secondary Ion Mass Spectrometry (SIMS) so as to include the boundary between the regions with different crystal structures. The boundary between the two layers is also the boundary between the regions with different crystal structures.

[0040] The average C content (yα, yβ) of the α layer and the β layer is determined for each layer by SIMS. That is, surface analysis by ion beam and etching by sputter ion beam are alternately repeated to measure the content in the depth direction. Specifically, in each layer, measurements are performed at a pitch of 0.01 μm or less in the layer thickness direction from a point 0.05 μm or more in the layer thickness direction to obtain an average value, and the average value calculated by performing this at least at five points is determined as the average C content of each layer.

[0041] In the analysis of electron backscattering diffraction (EBSD), if there is an orientation difference of 5 degrees or more between adjacent pixels, or if only one of the adjacent measurement points shows a wurtzite-type hexagonal structure or a NaCl-type face-centered cubic structure, the midpoint of these measurement points is regarded as a grain boundary.The area surrounded by the points regarded as a grain boundary is defined as one crystal grain.

[0042] However, a single pixel with an orientation difference of 5 degrees or more from all adjacent pixels is not treated as a crystal grain, but a pixel that is connected to two or more pixels is treated as a crystal grain. In this way, each crystal grain is determined and its crystal structure is identified, and the area ratio of crystal grains with hexagonal or cubic crystal structure in the layer thickness direction is obtained.

[0043] Once the boundaries of each layer are defined, the average layer thickness can be determined between the boundary regions of each defined layer, and the average Al content ratios (xα, xβ) of the α layer and the β layer can be determined by averaging the analysis results obtained by irradiating an electron beam using Auger electron spectroscopy (AES) to perform multiple (e.g., five or more) line analyses in the layer thickness direction.

[0044] Here, the method of calculating the average width and the average aspect ratio will be described. After identifying the grains as described above, the maximum length H of a certain grain i in the direction perpendicular to the surface of the tool base (layer thickness direction) is calculated. i , the grain width W, which is the maximum length horizontal to the tool base i , and area S i The average grain width is the average value of Wi. Also, the aspect ratio A of crystal grain i is i A i =H i / W i In this way, the aspect ratios A1 to A2 of at least 20 or more (i=1 to 20 or more) crystal grains in the observation field are calculated. n (n≧20) is determined, and the area-weighted average is calculated using [Equation 1] to determine the average aspect ratio A of the crystal grains.

[0045]

number

[0046] 5.Tool base (1)Material Any known substrate for this type of tool substrate may be used as the tool substrate as long as it does not impede the achievement of the above-mentioned object. For example, the substrate is preferably any one of cemented carbide (WC-based cemented carbide, WC, Co, and carbonitrides of Ti, Ta, Nb, etc.), cermet (mainly composed of TiC, TiN, TiCN, etc.), ceramics (titanium carbide, silicon carbide, silicon nitride, aluminum nitride, aluminum oxide, etc.), and cBN sintered body.

[0047] (2) Shape There are no particular limitations on the shape of the tool body as long as it is a shape that can be used as a cutting tool, and examples of the shape include the shape of an insert and the shape of a drill.

[0048] 6. Manufacturing method: The coating layer of the present invention can be obtained, for example, by supplying two types of reactive gases, for example, gas group A and gas group B having the following compositions, with a predetermined phase difference, onto a tool substrate or onto at least one underlayer of a Ti carbide layer, a nitride layer, a carbonitride layer, a carbonate layer and a carbonitride oxide layer on the tool substrate.

[0049] As an example of the gas composition of the reaction gas, the following can be shown, with % being volume % (the sum of gas group A and gas group B being taken as the whole).

[0050] (1) Reactant gas for forming the α layer Gas group A: NH3: 2.0-3.0%, H2: 50-60% Gas group B: AlCl3: 0.60-1.00%, TiCl4: 0.07-0.40%, C2H4:0.00~1.50%, N2:0.0~12.0%, H2:Remaining Reaction atmosphere pressure: 4.5~5.0kPa Reaction atmosphere temperature: 700~850℃ Supply cycle: 1.00~5.00 seconds Gas supply time per cycle: 0.26 to 0.40 seconds Phase difference between gas group A and gas group B: 0.10 to 0.20 seconds

[0051] (2) Reactant gas for forming the β layer Gas group A: NH3: 0.5-1.5%, N2: 0.0-5.0%, CH4:0.5~5.0%, C2H4:1.0~10.0%, H2: 20-40% Gas group B: AlCl3: 0.11-1.60%, Al(CH3)3: 0.00-0.24% MeClx (Me chloride): MeCl of one or more of the following elements: Ti, Si, Zr, V, Cr, Nb, Hf, Mn x However, each is 0.10 to 0.20% N2:2.0~10.0%, CH4:0.0~1.0%, C2H4: 0.0-1.5%, H2: balance Reaction atmosphere pressure: 4.5~5.0kPa Reaction atmosphere temperature: 650~850℃ Supply cycle: 1.00~5.00 seconds Gas supply time per cycle: 0.26 to 0.40 seconds Phase difference between gas group A and gas group B: 0.10 to 0.20 seconds EXAMPLES

[0052] Next, an embodiment will be described. Here, as an example of a coated tool of the present invention, we will describe an insert cutting tool in which a WC-based cemented carbide is used as the material for the tool base. However, the same applies when the above-mentioned TiCN-based cermet or cBN-based ultra-high pressure sintered compact is used as the material for the tool base, and the same applies when the coated tool is applied to the above-mentioned drills, end mills, etc. in terms of shape.

[0053] As raw material powders, WC powder, TiC powder, ZrC powder, TaC powder, NbC powder, Cr3C2 powder, TiN powder and Co powder, all having an average particle size of 1 to 3 μm, were prepared. These raw material powders were mixed to the composition shown in Table 1, wax was further added, and the mixture was mixed in acetone with a ball mill for 24 hours. After drying under reduced pressure, the mixture was pressed into a green compact of a predetermined shape at a pressure of 98 MPa. This pressed compact was vacuum sintered under conditions of holding at a predetermined temperature in the range of 1370 to 1470°C in a vacuum of 5 Pa for 1 hour. After sintering, WC-based cemented carbide tool substrates A to C having an insert shape according to ISO standard SEEN1203AFSN and WC-based cemented carbide tool substrates D to F having an insert shape according to ISO standard CNMG120408 were manufactured, respectively.

[0054] Next, each layer was formed on the surface of each of these tool substrates A to F by CVD using a CVD apparatus, and coated tools 1 to 20 of the present invention shown in Tables 10 and 11 were obtained. The film formation conditions are as shown in Tables 2 to 4, but are generally as follows: % in the gas composition is % by volume (the sum of gas group A and gas group B is taken as the whole).

[0055] (2) Reactant gas for forming the α layer Gas group A: NH3: 2.0-3.0%, H2: 50-60% Gas group B: AlCl3: 0.60-1.00%, TiCl4: 0.07-0.40%, C2H4:0.00~1.50%, N2:0.0~12.0%, H2:Remaining Reaction atmosphere pressure: 4.5~5.0kPa Reaction atmosphere temperature: 700~850℃ Supply cycle: 1.00~5.00 seconds Gas supply time per cycle: 0.26 to 0.40 seconds Phase difference between gas group A and gas group B: 0.10 to 0.20 seconds

[0056] (1) Reactant gas for forming the β layer Gas group A: NH3: 0.5-1.5%, N2: 0.0-5.0%, CH4:0.5~5.0%, C2H4:1.0~10.0%, H2: 40-50% Gas group B: AlCl3: 0.11-0.70%, Al(CH3)3: 0.00-0.25% MeCl x (Me chloride): 0.10~0.20%, (MeCl x (Specific names of Me chlorides are listed in Table 3) N2:2.0~10.0%, CH4:0.0~1.0%, C2H4: 0.0-1.5%, H2: balance MeCl x It is sufficient that the above percentage is satisfied for each Me component. Reaction atmosphere pressure: 4.5~5.0kPa Reaction atmosphere temperature: 650~850℃ Supply cycle: 1.00~5.00 seconds Gas supply time per cycle: 0.26 to 0.40 seconds Phase difference between gas group A and gas group B: 0.10 to 0.20 seconds

[0057] In addition, in the coated tools 1 to 20 of the present invention, the undercoat layer and the upper layer shown in Table 9 were formed under the film-forming conditions shown in Table 8.

[0058] For comparison purposes, comparative coated tools 1 to 10 shown in Tables 10 and 11 were manufactured by depositing films on the surfaces of tool substrates A to F using a CVD apparatus under the conditions shown in Tables 5 to 7. Comparative coated tools 1 to 6 were formed with undercoat layers and upper layers shown in Table 9 under the deposition conditions shown in Table 8.

[0059] For the coated tools 1 to 20 of the present invention and the comparative coated tools 1 to 10, the composition of each layer, the average layer thickness, the area ratio of crystal grains with cubic crystal structure and hexagonal crystal structure, and the area ratio of crystal grains with NaCl type face-centered cubic structure were determined using the methods described above, and the results are shown in Tables 10 and 11.

[0060] [Table 1]

[0061] [Table 2]

[0062] [Table 3]

[0063] [Table 4]

[0064] [Table 5]

[0065] [Table 6]

[0066] [Table 7]

[0067] [Table 8]

[0068] [Table 9]

[0069] [Table 10]

[0070] [Table 11]

[0071] In addition, the following notes apply to Tables 10 and 11. Note 1: In the formation of the α-layer and β-layer of the coated tools 5 and 15 of the present invention, lamination of the α-layer / β-layer was repeated twice to form a total of four layers. The average layer thicknesses Lα and Lβ are the respective total values. Note 2: The area ratio of hexagonal crystals is the percentage of crystal grains that have a hexagonal crystal structure. Note 3: The area ratio of cubic crystals is the area ratio (%) of crystal grains with a NaCl-type face-centered cubic structure. Note 4: "Only the flank" means that the coating layer is only the α layer and is marked with a circle, otherwise it is marked with an x. Note 5: Comparative coated tools 3, 4, 8, and 9 did not have an α layer, but only a β layer ("-" indicates that it does not contain or that there is no applicable item). Note 6: The total of the compositions may be less than or greater than 1 due to rounding to the third decimal place. Note 7: "*" does not satisfy the provisions of claim 1.

[0072] Next, the following cutting test 1 (coated tools 1-10 of the present invention, comparative coated tools 1-5) and cutting test 2 (coated tools 11-20 of the present invention, comparative coated tools 6-10) were conducted on the coated tools 1-20 of the present invention and comparative coated tools 1-10, and the results are shown in Tables 12 and 13, respectively.

[0073] 1. Cutting test 1: Dry high-speed face milling, center cut cutting Cutter diameter: 125mm Workpiece: JIS SCM440, width 100mm, length 400mm block material Rotational speed: 891 / min Cutting speed: 350m / min Cutting depth: 2.0mm Feed per blade: 0.2mm / blade Cutting time: 8 minutes (Normal cutting speed is 150~250m / min)

[0074] 2. Cutting test 2: Dry high-speed intermittent cutting Workpiece: JIS SCM440 round bar with four longitudinal grooves spaced equally along the length Cutting speed: 300m / min Cutting depth: 1.5mm Feed: 0.2mm / rev Cutting time: 5 minutes (Normal cutting speed is 150~200m / min)

[0075] [Table 12]

[0076] [Table 13]

[0077] From the results shown in Tables 12 and 13, the coated tools 1 to 20 of the present invention all have excellent chipping resistance in the coating layer, and therefore do not suffer from thermal cracking or chipping, and exhibit excellent wear resistance over a long period of time, even when used in high-speed intermittent cutting of cast iron, etc. In contrast, the comparative coated tools 1 to 10, which do not satisfy even one of the requirements for the coated tools of the present invention, suffer from chipping when used in high-speed intermittent cutting of cast iron, etc., and reach the end of their service life in a short period of time. [Industrial Applicability]

[0078] As described above, the coated tool of the present invention can be used as a coated tool for high-speed interrupted cutting of materials including alloy steel and exhibits excellent wear resistance over a long period of time, so that it is possible to satisfactorily meet the needs for improving the performance of cutting equipment, reducing labor and energy consumption in cutting work, and further reducing costs. [Explanation of symbols]

[0079] 1 Tool base 2 α layer (AlTiCN layer) 3 β layer (AlMeCN layer)

Claims

1. A surface-coated cutting tool having a tool base and a coating layer provided on the surface of the tool base, 1) The coating layer has one or more laminate layers each having an α layer on the tool substrate side and a β layer on the tool surface side as a laminate unit layer, 2) The α layer includes a composite nitride layer or composite carbonitride layer of Al and Ti having an average layer thickness of 1.0 to 20.0 μm, and the average composition of the layer is represented by the formula: (Al xα Ti 1 -xα ) (C yα N 1-yα ), xα is 0.60 to 0.95, yα is 0.000 to 0.015, 3) The area ratio of crystal grains having a NaCl type face-centered cubic structure in the α-phase is 70% or more; 4) The β layer includes a composite carbide layer or composite carbonitride layer of Al and Me (Me is one or more elements selected from Ti, Si, Zr, V, Cr, Nb, Hf, and Mn) having an average layer thickness of 0.5 to 5.0 μm, and the average composition is represented by the formula: Al xβ Me yβ C zβ N 1-xβ-yβ-zβ When expressed as above, xβ / (xβ+yβ) is 0.70 to 0.95, zβ / (xβ+yβ) is 0.15 to 3.00, and xβ+yβ is 0.15 to 0.60, 4) The total area ratio of crystal grains having a hexagonal crystal structure of wurtzite type and crystal grains having a face-centered cubic structure of NaCl type in the β-phase is less than 30%. A surface-coated cutting tool comprising:

2. 2. The surface-coated cutting tool according to claim 1, wherein the rake face of the surface-coated cutting tool has a coating layer including an α layer and a β layer, and the flank face has a coating layer including only an α layer.

3. 3. The surface-coated cutting tool according to claim 1, wherein the α layer has a columnar crystal structure, the columnar crystal grains having an average grain width W of 0.1 to 1.2 μm and an area-weighted average aspect ratio A of 2.0 to 10.0.

Citation Information

Patent Citations

  • Coating, cutting tool and method of producing coating

    JP2015124407A

  • Hard coating, cutting tool and method for manufacturing hard coating

    JP2016003369A

  • Surface-coated cutting tool allowing hard coating layer to exhibit superior chipping resistance

    JP2016049573A

  • Surface coated cutting tool with hard coating layer having excellent chipping resistance and peel resistance

    JP2018118346A

  • Surface-coated cutting tool

    JP2020104255A